ANALISIS LITERASI DIGITAL DALAM PEMBELAJARAN PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Apriliya, Thiara Sati; Purwaningsih, Endang; Basri, Muhammad (Universitas Tanjungpura, 2024)
This study aims to analyze digital literacy in learning. To analyze digitalliteracy in learning, eight essential aspects are needed, including cultural,cognitive, constructive, communicative, selfconfident, creative, critical, andresponsible. This analysis uses an independent variable, namely digitalliteracy in learning in order to describe and obtain clear informationregarding digital literacy in learning for Economics Education students atFKIP UNTAN. Data collection in this study was carried out by in-depthinterviews. This study uses a snowball sampling technique and the methodused is a qualitative research method that focuses on in-depth analysisrelated to digital literacy in learning. The results of the study show thatdigital literacy in student learning related to eight aspects has been carriedout well but is still not fully optimal. Knowing about various technologiesand understanding how to use them, having awareness and the impact thatwill be made by the students themselves. With digital literacy in learning,students can save time, learn faster, always get the latest information andcan make better decisions.